Molecular detection of small ruminant piroplasmosis and first report of Theileria luwenshuni (Apicomplexa: Theileridae) in small ruminants of Pakistan - Nasreen; Khan, Adil; Niaz, Sadaf; Shah, Mir Hassan; Khan, Aisha; Ahmed, Haroon; Aktas, Munir (Academic Press Inc Elsevier Science, 2020)
Theileriosis is a widespread and economically important disease of small ruminants in Pakistan. Ruminants are the intermediate hosts in the lifecycle of Theileria spp., with ticks of the family Ixodidae being the definitive hosts. To better understand the distribution and prevalence of theileriosis in Pakistan, a molecular survey was performed in small ruminants from the Lower Dir district of the Khyber Pakhtunkhwa province. A total of 200 healthy sheep and goats were screened from Maidan, Samar Bagh and Munda districts of district Dir Lower, Pakistan during December (2017) to April (2018). DNA samples were screened through nested PCR using universal primers. The amplified 492-498 bp amplicon was subjected to RLB analysis which was based on the hypervariable of the 18S rRNA gene to test for the presence of genotypes of Theileria in blood samples. A phylogeny was constructed to determine the species of Theileria genotypes. Nested PCR results indicated 53.5% prevalence of one or more Theileria genotypes in the blood of the host animal. From RLB assay, 27 animals (13.5%) showed infection with only a single species of Theileria while 80 animals (40%) showed coinfection by multiple Theileria spp. Based on the 18S rRNA phylogeny, the unknown genotype is of the species Theileria luwenshuni and is closely related to Chinese isolates. The present finding is the first report on molecular diagnosis of Theileria luwenshuni in small ruminants in Pakistan.
Keywords: Theileria luwenshuni; Small ruminant; Phylogenetic analysis; Pakistan